2016
DOI: 10.1111/puar.12610
|View full text |Cite
|
Sign up to set email alerts
|

University Rankings: Evidence and a Conceptual Framework

Abstract: University ranking has high public visibility, the ranking business has flourished, and institutions of higher education have not been able to ignore it. This study of university ranking presents general considerations of ranking and institutional responses to it, particularly considering reactions to ranking, ranking as a self‐fulfilling prophecy, and ranking as a means of transforming qualities into quantities. The authors present a conceptual framework of university ranking based on three propositions and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 53 publications
2
26
1
1
Order By: Relevance
“…On the individual level, performance indicators could induce the substitution of extrinsic motivations for intrinsic motivations, a problem referred to as goal displacement [ 9 , 23 ]. In addition, citation metrics have been argued to be more likely to consecrate stable institutional prestige hierarchies than to foster inter-organizational competition [ 15 , 24 ]. More generally, rankings in higher education are viewed as reactive, in that they create the social order they are supposed to measure [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the individual level, performance indicators could induce the substitution of extrinsic motivations for intrinsic motivations, a problem referred to as goal displacement [ 9 , 23 ]. In addition, citation metrics have been argued to be more likely to consecrate stable institutional prestige hierarchies than to foster inter-organizational competition [ 15 , 24 ]. More generally, rankings in higher education are viewed as reactive, in that they create the social order they are supposed to measure [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The last threat is the periodical publication of the rankings, which provokes concern in many universities about the systematic collection of data that allows universities to rise in the rankings year by year, converting the means (measurement) into the goal (to be measured). However, after many years of reports, we already know that results are very stable: the correlation (r Pearson) of results from one year to the next is up to 0,96 (Fowles, Frederickson, & Koppell, 2016b). Thus, what we have has been a persistent system of exalting the top universities and of disparaging the rest.…”
Section: Threatsmentioning
confidence: 97%
“…This growing presence of rankings in the main databases of the international scientific literature reveals that the publication of university rankings is of undoubted interest to the university community, as well as to society in general. This popularity of the rankings is fuelled by university managers and policy makers, as well as their recipients (Fowles, Frederickson, & Koppell, 2016a;Millot, 2015;O'Connell, 2015). However, these articles contain criticisms by scientists and experts, especially regarding methodological matters.…”
Section: Introductionmentioning
confidence: 99%
“…This makes research reputation critical to creating a virtuous circle in which more research funding generates good research outcomes, and enhances desirability further (Morphew et al, ). If reputational winners also derive direct financial benefits through an ability to charge higher fees, or attract more students, this makes sustained research excellence more affordable and can explain the observed stability of US rankings (Fowles et al, ; Sauder & Lancaster, ).…”
Section: Introductionmentioning
confidence: 99%